KERUSAKAN HUTAN RAWA GAMBUT DI SEMANJUNG KAMPAR: STUDI TENTANG MNCs DAN NEGARA - Siti Aminah (Jurnal Kebijakan Publik, 2016)
Damage Peat Swamp Forest in Kampar: Study of the MNCs and the State. This research tryto describe the problem of destruction of forest (deforestation) is very influential on the worldenvironmental security issues. The destruction of forests (deforestation), especially in Riau Kamparpeninsula until involves two actors that play a role that MNCs (PT.RAPP) and State ( Indonesia )with this problem. This research uses group -level analysis and dependency theory argued byTheotonio Dos Santos.This research used qualitative methods. The data was collecting by usedlibrary research tehniques through secondary data and primery data where this techniques is collectingdata sourced from the literature like books, websites,official publictions, and journal. The resesrchshows that the forest degradation (deforestation) peat swamp on Kampar peninsula,Riau. Their rolebetween the MNCs is PT.RAPP ( Company Limited Riau Andalan Pulp and Paper ) and the State ,namely the Indonesian government as a policy-making resulted in problems for the country and theworld that have a negative impact causing global warming. Backed by factors that occur as naturaldisasters land migrate happens less and the major impact is encroachment and Entrepreneursconcessions Forest ( HPH ) that resulted in overlapping policies and rules given by the governmentof the influence of the owners of the company’s capital, and weak enforcement law.